Lilium pumilum stress-responsive NAC transcription factor LpNAC17 enhances salt stress tolerance in tobacco - Wang, Yiping; Cui, Ying; Liu, Bin; Wang, Ying; Sun, Shaoying; Wang, Jingwen; Tan, Mengmeng; Yan, Hao; Zhang, Yanni (Frontiers in Plant Science, 2022)
Lilium pumilum is an annual herb with ornamental edible and medicinal value. It is an excellent wild germplasm resource with wide distribution and strong resistance. The NAC family of transcription factors is unique to higher plants. The NAC family not only plays a regulatory role in plant growth and development, but also participates in plant responses to biotic and abiotic stresses. The LpNAC17 gene of L. pumilum was cloned and transformed into tobacco to investigate the response of transgenic tobacco to salt stress. The results showed that the contents of net photosynthetic rate and chlorophyll in LpNAC17 over-expressed tobacco were higher than those in the control group, while the contents of stomatal conductance, transpiration rate and intercellular CO2 concentration were lower than those in the control. The activity of superoxide dismutase, peroxidase, catalase and the content of proline in LpNAC17 over-expressed tobacco were higher than those in the control, while the content of malondialdehyde, superoxide anion and hydrogen peroxide were lower than that in the control. Nitro-blue tetrazolium staining and 3,3′-diaminobenzidine tissue localization also showed that the content of O2- and H2O2 in transgenic tobacco was lower. The expression levels of NtSOD, NtPOD, NtCAT, NtHAK1, NtPMA4 and NtSOS1 in transgenic tobacco were higher than those in control.